Analysis of pregnancy outcomes for survivors of the vanishing twin syndrome after in vitro fertilization and embryo transfer. (August 2016) - Zhou, Lina; Gao, Xiaohong; Wu, Yu; Zhang, Zhenbo
Abstract: Objective: The purpose of this study was to compare pregnancy outcomes of in vitro fertilization (IVF) singletons diagnosed with vanishing twin syndrome with control pregnancies originating as singleton pregnancies and with twin pregnancies. Study design: The current research included 206 survivors of a vanished co-twin, 1730 primary singletons and 662 primary twins. The study group was subdivided according to gestational age at the time of vanishing to give groups of early (≤12 weeks, group A) and late (>12 weeks, group B) survivors. Pregnancy outcomes were compared among study groups and controls. Results: 10.54% of all IVF singleton deliveries originated from a twin gestation. Group A showed similar mean gestational age ( P  = 0.148) but higher proportion of preterm delivery ( P  = 0.000), extremely preterm delivery ( P  = 0.000), low birth weight ( P  = 0.000) and very low birth weight ( P  = 0.000) when compared with singleton controls. The comparison between group B and the singleton controls revealed dramatically higher frequency of preterm delivery ( P  = 0.000), extreme preterm delivery ( P  = 0.000), low birth weight ( P  = 0.000), very low birth weight ( P  = 0.000) and neonatal mortality ( P  = 0.000). When compared with twin controls, group A showed lower risk of adverse pregnancy outcomes; in contrast, group B still showed significant higher adverse risk. Conclusions: IVF singletons with a vanished co-twin had a higher rate of adverse pregnancy outcomes in terms of preterm delivery and low birth weight, compared with IVF pregnancies that were originally singleton and twins, and the risk is increased with increasing gestational age at the time of vanishing.